Development and adaptation of a strength-based job interview training tool for transition age youth on the autism spectrum using community engaged methods - Genova, Helen M.; Haas, Mikayla; Chen, Yu-Lun; Elsayed, Heba E.; McGrath, Robert E.; Smith, Matthew J. (Frontiers in Psychiatry, 2023)
Kessler Foundation Strength Identification and Expression (KF-STRIDE) is a strength-based job interview training tool developed for young adults on the autism spectrum. The intervention is based on a positive psychology framework to increase knowledge of character strengths, and how to relate them to a future employer. The current study sought to evaluate the acceptability, usability and feasibility of KF-STRIDE, as well as to guide adaptations to improve the tool's ability to meet the needs of those on the spectrum. Mixed methods (post-intervention surveys, and semi-structured interviews with key stakeholders) were used to inform the evaluation and consequent adaptations of KF-STRIDE. The major findings of the study were that KF-STRIDE was found to be largely acceptable and usable. Importantly, however, our qualitative analysis revealed modifications that could help to better suit the needs of young adults on the spectrum, which included the incorporation of additional skills (i.e. etiquette, practicing hygiene) and more opportunities to practice job interviewing. Thus, we altered the implementation of the intervention to be web-based to improve accessibility. We incorporated the presence of an animated character to deliver the content, to eliminate the need for a highly trained interventionist. Thus, KF-STRIDE was modified to increase access by incorporating feedback from the autism community. Future directions include assessing the efficacy of KF-STRIDE in young adults on the spectrum to identify whether employment outcomes are improved after using the tool.